2018
DOI: 10.20344/amp.9996
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression and Academic Performance: A Study Amongst Portuguese Medical Students Versus Non-Medical Students

Abstract: Introduction: The aim of the study is to assess the prevalence of anxiety and depressive symptoms in Portuguese medical students compared to students of other faculties, and the possible impact those symptoms have on academic performance.Material and Methods: A cross-sectional study was conducted in a sample of 750 students: 512 medical students and 238 nonmedical students. All students anonymously completed a socio-demographic survey and the Hospital Anxiety and Depression Scale (HADS). Statistical analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
59
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 28 publications
12
59
0
10
Order By: Relevance
“…Our research found a link between low self-assessment of academic performance and noticing symptoms that might had suggested depression during the course of medical studies. Similar results were obtained by Moreira de Sousa J et al who found a link between occurrence of depressive symptoms and lower curricular average grade among medical students [10]. Analogical link was described by Çelik N et al in a research conducted among 445 Turkish medical students [11].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our research found a link between low self-assessment of academic performance and noticing symptoms that might had suggested depression during the course of medical studies. Similar results were obtained by Moreira de Sousa J et al who found a link between occurrence of depressive symptoms and lower curricular average grade among medical students [10]. Analogical link was described by Çelik N et al in a research conducted among 445 Turkish medical students [11].…”
Section: Discussionsupporting
confidence: 86%
“…Analogical relationship was described by Moreira de Sousa J et al among 521 Portuguese medicine students . [10] Similar link was found in case of repeating a year. Our research found a link between low self-assessment of academic performance and noticing symptoms that might had suggested depression during the course of medical studies.…”
Section: Discussionsupporting
confidence: 64%
“…It is a handy and reliable tool for identifying anxiety and depression. HADS has been used in the general population, in general hospital patients, in cancer care units, and even in patients with acquired immune deficiency syndrome and in the student population (28). The scale comprises a total of fourteen questions out of which seven concern the development of anxiety disorder and the remaining seven concern depression (29).…”
Section: Data Collectionmentioning
confidence: 99%
“…Studies among pharmacy students showed that stress was negatively correlated with quality of life (Marshall, Allison, & Nykamp, 2008;Eisenberg, Golberstein, & Hunt, 2009;Opoku-Acheampong et al, 2017). Depression has also been shown to be negatively associated with academic performance among undergraduate students (Al-qaisy, 2011; Khanam & Bukhari, 2015;Moreira de Sousa, Moreira, & Telles-Correia, 2018). Depression and anxiety were also associated with poor sleep quality and deterioration in the quality of life (Cramer, Torgersen, & Kringlen, 2005;Oh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%